THE IMPACT OF CUSTOMER REVIEWS ON BRAND TRUST AND CONSUMER PURCHASE DECISIONS ON E-COMMERCE PLATFORMS - Muhammad Fikry Januar; Sena Kurniawan; Imma Ismaniar (Journal of Applied Digital Business Management, 2025)
This study examines the critical role of Online Customer Reviews (OCR) in shaping consumer purchase decisions in the e-commerce marketplace. In the current digital ecosystem, OCR functions as a form of Electronic Word-of-Mouth (e-WOM) that influences risk perception, brand trust, and purchase intention. This research aims to quantitatively analyze how the dimensions of OCR specifically Valence, Volume, and Quality affect Brand Trust, which, in turn, impacts Purchase Decisions across various e-commerce platforms. Data were collected from 300 active e-commerce platform users through an online survey. The analysis, conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), revealed that Positive Valence (β =0.493, p < 0.001) and Volume of OCR (β =0.256, p < 0.01) have a significant and positive influence on Brand Trust. Brand Trust is proven to be a critically important mediator, significantly and positively affecting Purchase Decisions (β a=0.689, p < 0.001). Importantly, the textual Quality of the reviews was found to be non-significant in influencing Brand Trust (β =0.071, p > 0.05). These findings underscore the importance of managing online reputation and providing a platform that facilitates transparent consumer communication as a competitive strategy in the e-commerce sector.